21.3 dBm 18.5 GHz‐BW 8‐way E‐band power amplifier in 28 nm high performance mobile CMOS. Issue 19 (1st September 2017) - Zhao, Dixian; Reynaert, Patrick
Abstract : A fully integrated broadband E‐band power amplifier (PA) is implemented in 28 nm CMOS process. To enhance the output power ( P OUT ), an 8‐way differential series‐parallel power combiner is used together with the neutralised bootstrapped cascode amplifier topology. The unit PAs are realised by both NMOS and PMOS transistors, respectively, which cancel the amplitude‐to‐phase modulation (AM‐PM) distortion due to non‐linear gate‐to‐source capacitance ( C GS ) of NMOS and PMOS transistors under large input voltage amplitude. The presented PA achieves a saturated output power ( P SAT ) of 21.3 dBm with more than 18.5 GHz −3 dB small‐signal bandwidth (BW−3 dB ).